YES(?,O(n^2)) Problem: f(f(x)) -> g(f(x)) g(g(x)) -> f(x) Proof: Complexity Transformation Processor: strict: f(f(x)) -> g(f(x)) g(g(x)) -> f(x) weak: Matrix Interpretation Processor: dimension: 1 max_matrix: 1 interpretation: [g](x0) = x0 + 1, [f](x0) = x0 orientation: f(f(x)) = x >= x + 1 = g(f(x)) g(g(x)) = x + 2 >= x = f(x) problem: strict: f(f(x)) -> g(f(x)) weak: g(g(x)) -> f(x) Matrix Interpretation Processor: dimension: 2 max_matrix: [1 1] [0 1] interpretation: [1 1] [0] [g](x0) = [0 1]x0 + [1], [1 1] [1] [f](x0) = [0 1]x0 + [1] orientation: [1 2] [3] [1 2] [2] f(f(x)) = [0 1]x + [2] >= [0 1]x + [2] = g(f(x)) [1 2] [1] [1 1] [1] g(g(x)) = [0 1]x + [2] >= [0 1]x + [1] = f(x) problem: strict: weak: f(f(x)) -> g(f(x)) g(g(x)) -> f(x) Qed